درجة توافر مهارات التفكير الناقد في محتوى مادة الدِّراسات الاجتماعية للصف الرابع الأساسي من وجهة نظر معلمي الصفوف (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف البحث إلى تعرُّف درجة توافر مهارات التفكير الناقد في محتوى كتاب: (مادة الدِّراسات الاجتماعية للصف الرابع الأساسي) من وجهة نظر معلمي الصفوف، إضافةً إلى تحديد دلالة الفروق بين متوسطات استجابات معلمي الصفوف حول درجة توافر مهارات التفكير الناقد في محتوى الكتاب وفقاً لمتغيرات الجنس والمؤهل الدراسي وسنوات الخبرة في التدريس. استخدمت الباحثة المنهج الوصفي التحليلي كونه يناسب هذا النوع من الأبحاث، وقامت بإعداد استبانة في ضوء مهارات التفكير الناقد وطبقتها على (92) معلماً ومعلمةً من معلمي الصف الرابع الأساسي في مدينة اللاذقية. أظهرت نتائج البحث أن درجة توافر مهارات التفكير الناقد ككل في محتوى كتاب مادة الدراسات الاجتماعية للصف الرابع الأساسي من وجهة نظر معلمي الصفوف جاء بدرجة متوسطة، إذ توفرت مهارات (تعرف الافتراضات، التفسير، الاستنباط) بدرجة متوسطة، ومهارة "الاستنتاج" بدرجة عالية ومهارة "تقويم الحجج" بدرجة متدنية، ولم تُوجد فروق ذات دلالة إحصائية بين متوسطات استجابات معلمي الصفوف حول درجة توافر مهارات التفكير الناقد في محتوى الكتاب تُعزى لمتغيري الجنس وسنوات الخبرة في التدريس، في حين كانت الفروق ذات دلالة إحصائية بين متوسطات استجابات معلمي الصفوف وفقاً لمتغير المؤهل الدراسي لصالح المعلمين الذين قاموا بتعميق تأهيلهم التربوي. The research aims at identifying the degree of availability of the critical thinking skills in the content of fourth- grade social studies in the views of class teachers. It also seeks to determine the significance of differences between the responses of the teachers of classes about the degree of availability of the critical thinking skills in the content of the textbook, which is attributed to the variances of sex, qualification and  the number of years of experience. The researcher used the descriptive analytical methodology, and prepared a questionnaire in the light of the critical thinking skills and applied it on (92) class teachers from the teachers of fourth- grade in Lattakia city. The results showed that the availability of these basic thinking skills as a whole in the content of fourth- grade social studies textbook in the views of class teachers was of an average degree; the skills of knowing hypotheses, interpreting, and deducting were available in an average degree, while the skill of inferring was available in a higher degree, and the skill of evaluating arguments was available in a low degree. Also, there were not significant statistical differences between the responses of the teachers of classes about the role of availability of the basic thinking skills in the content of the textbook, which is attributed to the variances of sex and the number of years of experience, but there were significant statistical differences between the responses of the teachers of classes about the degree of availability of the basic thinking skills in the content of the textbook, which is attributed to the variance of qualification in favor of teachers who have deepened their education rehabilitation.